Volcanic Soils: Their Characteristics, Management Practices, and Potential Sollution for Water Pollution - Rendy Anggriawan; Nuryana Ariska Salsabilla; Imelda Ayu Prahesti (SEAS (Sustainable Environment Agricultural Science), 2023)
Volcanic soils are formed from materials originating from volcanic eruptions, and with various pedogenic processes occurring, volcanic soils have unique physical, chemical, and biological characteristics. This paper aims to review the characteristics of volcanic soils, constraints, management practices, and their potential as adsorbents for contaminants. The paper was based on secondary information using a systematic review. The studies carried out include identifying manuscripts, analyzing report data, critically assessing the topic, and combining the results of relevant published manuscripts. The issues raised include data on volcanic soils, management practices, water pollution, and using volcanic soils as an environmentally friendly adsorbent. Colloidal compounds in the clay fraction of volcanic soils generally contain active Al and Fe compounds, allophane, imogolite, ferrihydrite, or Al/Fe-humus complex, and together with opaline silica. The volcanic soil material produces a pool of Al and Fe solid phases with high reactivity, which contributes to the unique physicochemical properties of Andisol. The main problem chemically is the high adsorption of phosphate and nitrate ions which causes the fertilization process to be inefficient. The main problem affects the adsorption of phosphate and nitrate on agricultural lands, so fertilization becomes inefficient. However, the high reactivity of volcanic soils can be used as a basic pollutant adsorbent. This is quite a promising opportunity, given the wide distribution of volcanic soils, so this resource is a very prospective candidate as an adsorbent material in water purification.